Umano, troppo umano...o no? Robot, androidi e cyborg nel “mondo del diritto” (prime notazioni) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
Robotics opens up new opportunities in many different fields, but also possibly unintended consequences. Thus, providing a legal framework might encounter some difficulties. What/who is a robot? It is hard to give a definition: they are “machines” interacting with surrounding environment but are they to be considered responsible for their actions? And humanoid robots are entitled to “politically correctness”? Concepts like informed consent, privacy or even the definition of health or illness require new understandings, in the light of new scenarios drawn by empowerment, enhancement or brain computer interfaces, welcoming new chances but fearing possible consequences of a kind of dehumanisation.
Keywords: robotics and the law; brain computer interfaces; liability; enhancement; fundamental rights